LATE CARNIAN-EARLY NORIAN AMMONOIDS FROM THE GSSP CANDIDATE SECTION PIZZO MONDELLO (SICANI MOUNTAINS, SICILY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
A small collection of ammonoids from the Upper Triassic Scillato Formation at Pizzo Mondello (Agrigento, Sicily) is studied. The specimens were collected in a framework of a project aimed at providing an integrated high-resolution bio-chronostratigraphic support to the Upper Carnian-Norian magnetostratigraphic scale defined at this site, that is located in an historical area from which G.G. Gemmellaro collected the Upper Triassic of ammonoids monographed at the beginning of the XX century. The specimens from Pizzo Mondello were bed-by-bed sampled and represent the first collection of Upper Triassic ammonoids described from Sicily since Gemmellaro time. Quite several levels of the Pizzo Mondello section yielded ammonoids, but very few levels have provided more than one specimen. Due to the scarcity of specimens the taxonomic analysis has been complex because Gemmellaro, who described 166 new species, did not explain the variability of many of his taxa. Sixsteen taxa belonging to eleven genera are described. They include Placites sp. ind., Discotropites plinii (Mojsisovics), Anatropites sp., Microtropites cf. paronai, Metathisbites cf. affinis, Hyattites aff. praefloridus, Projuvavites boehmi (Gemmellaro), Projuvavites inflatus (Gemmellaro), Gonionotites cf. italicus, Gonionotites aff. recuperoi, Dimorphites noricus n. sp., Dimorphites selectus Mojsisovics, Dimorphites sp., Pregriesbachites n. gen. , P. bukowskii (Gemmellaro), Discophyllites insignis. Among the new taxa, Dimorphites noricus n. sp. formalizes the nomen nudum “Dimorphites n. sp. 1” quoted in literature for several years, that is index of the lowest subzone of the Norian stage.The small collection document the Discotropites plinii and Gonionotites italicus subzones of the uppermost Carnian Spinosus Zone and the Dimorphites noricus and D. selectus subzones of the Jandianus Zone, the first zone of the Lower Norian. This chronostratigraphic classification firmly tie the Pizzo Mondello succession to the Tethyan chronostratigraphic scale, and is crucial for the calibration of the Halobia and conodont bioevents identified in the section. The chronostratigraphic correlations based on ammonoids of the Pizzo Mondello section with Feuerkogel (Austria), Jomsom (Nepal), West Union Canyon (Nevada, USA) and Black Bear Ridge (British Columbia, Canada) is discussed. These are the most complete ammonoid-bearing sections in the world spanning the Carnian/Norian boundary, but all of them show a discrete distribution of ammonoid-bearing beds across the boundary. Ammonoid will not provide the primary marker event for the definition of the GSSP of the Norian, but they are crucial for the selection of the most significant events.
Keywords: Upper Triassic; Carnian/Norian boundary; Ammonoids; Biostratigraphy; Sicily; Sicanian Domain; Scillato Formation